2013
DOI: 10.1186/1472-6874-13-26
|View full text |Cite
|
Sign up to set email alerts
|

“It’s not easy to acknowledge that I’m ill”: a qualitative investigation into the health seeking behavior of rural Palestinian women

Abstract: BackgroundThis qualitative study sets to fill a gap in knowledge by exploring the health seeking behaviour of rural women living in the occupied Palestinian territories (oPt). The existing literature on the oPt has so far focused on unravelling the country’s epidemiological and health system profile, but has largely neglected the assessment of factors shaping people’s decisions on health care use.MethodsBased on a conceptual framework rooted in the Anderson behavioural model, we conducted 30 semi-structured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 57 publications
2
14
0
Order By: Relevance
“…Many women and nurses in this study viewed health as the absence of symptoms; they frequently postponed seeking medical assistance and used self-prescribed medicine or alternative medicine. This response has also been found in other countries including Pakistan, UAE and Palestine (Anwar, Green, Norris, & Bukhari, 2015;Elobaid et al, 2016;Majaj, Nassar, & De Allegri, 2013). The GPs participating in this study also confirmed that women with BC often presented at the advanced stage of the disease when they experienced severe pain or found large breast lumps that could not be managed at home.…”
Section: Muslims and Viewed Health As One Of The Greatest Blessings Thatsupporting
confidence: 84%
“…Many women and nurses in this study viewed health as the absence of symptoms; they frequently postponed seeking medical assistance and used self-prescribed medicine or alternative medicine. This response has also been found in other countries including Pakistan, UAE and Palestine (Anwar, Green, Norris, & Bukhari, 2015;Elobaid et al, 2016;Majaj, Nassar, & De Allegri, 2013). The GPs participating in this study also confirmed that women with BC often presented at the advanced stage of the disease when they experienced severe pain or found large breast lumps that could not be managed at home.…”
Section: Muslims and Viewed Health As One Of The Greatest Blessings Thatsupporting
confidence: 84%
“…Social obligations, family responsibilities and burden of work were common barriers that influenced decision to seek care. It is well known that women prioritize other matters and neglect their own health (Bonsu and Ncama, 2019;Majaj et al, 2013).This is similar in case of women with breast cancer as well where parenting and other family and social issues influence their health seeking behaviour (Bonsu and Ncama, 2019;Moodleyet al, 2016;Vanderpool et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…The model has been widely used for understanding and structuring results about access to and utilization of health services [ 15 ]. Modified versions have been adopted in qualitative studies to assess healthcare utilization from stakeholder perspectives other than actual users, e.g., relatives, caregivers [ 16 , 17 , 18 ], medical staff, service providers, and key informants [ 19 , 20 , 21 ]. For instance, a qualitative study similar to the present one investigated medication adherence in patients with rheumatoid arthritis by interviewing rheumatologists, and mapped discovered determinants into Andersen’s model [ 22 ].…”
Section: Introductionmentioning
confidence: 99%